Legal Protection and Legal Certainty in International Electronic Contract Dispute Resolution - Hadi Purnomo (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This research analyses legal protection and legal certainty in the resolution of international electronic contract disputes through Online Dispute Resolution (ODR). The study aims to examine the legal position of electronic contracts in international trade, the implementation of ODR in cross-border dispute settlement, and the legal certainty provided to parties involved in digital transactions. This research employs normative legal research using statutory, conceptual, and comparative approaches. Primary legal materials include Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016, the UNCITRAL Model Law on Electronic Commerce 1996, and UNCITRAL Technical Notes on Online Dispute Resolution. Secondary legal materials were obtained from books, journals, and previous legal studies. The analysis was conducted qualitatively through the interpretation of legal norms, principles, and doctrines related to international electronic contracts and digital dispute resolution. The results indicate that ODR provides effectiveness, efficiency, and flexibility in resolving international electronic contract disputes. However, its implementation still faces challenges related to jurisdiction, recognition of electronic decisions, digital data security, and the lack of harmonized regulations. The novelty of this research lies in integrating legal protection, legal certainty, and the legitimacy of digital decisions within international electronic contract dispute resolution systems.